MINERALOGY AND GEOCHEMISTRY OF BAGINDA HILL GRANITOID, BELITUNG ISLAND, INDONESIA - Ikhsan, Naufal (DEPARTEMEN TEKNIK GEOLOGI FT UGM, 2016)
Granitoid spread outs widely throughout Belitung Island, Indonesia. The distribution of granitoid in northwestern part of Belitung Island is associated with tin deposit. In southwestern part of Belitung Island at Baginda Hill, however the granitoid is extremely low tin contents (Sn concentrations: 2-3 ppm). Study of mineralogy characteristics and geochemistry at Baginda Hill, therefore is important in understanding the granitoid variation and its petrogenesis. The petrography observation showing monzogranite and syenogranite are variations of granitoid at Baginda Hill with presence of quartz, plagioclase, alkali feldspar, biotite, hornblende, and accessory minerals such as fluorite, rutile, zircon and opaque minerals. Harker diagrams of the granitoid reveal SiO2 has negative correlation with oxide major such as TiO2, Al2O3, Fe2O3, CaO, K2O, Na2O, MnO, MgO dan P2O5 reflecting influence of magmatic fractionation. Magmatic affinity of the granitoid is kalk-alcaline with high K calc alkaline and shoshonitic. Metalumieous with tipe-I is its typology of the granitoid. Plotting results of trace element Rb versus Y+Nb dan Nb versus Y suggest that Baginda Hill granitoid occurred on VAG (Volcanic Arrc Granites) setting which related to orogenic and associated with subduction. Key words : Baginda Hill, calk-alkalin, monzogranite, shoshonitic, syenogranite, Volcanic Arc Granite, Belitung